2015
DOI: 10.1017/s0022377815000380
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of hot tail runaway electron generation in TEXTOR disruptions

Abstract: Experimental evidence supporting the theory of hot tail runaway electron (RE) generation has been identified in TEXTOR disruptions. With higher temperature, more REs are generated during the thermal quench. Increasing the RE generation by increasing the temperature, an obvious RE plateau is observed even with low toroidal magnetic field (1.7 T). These results explain the previously found electron density threshold for RE generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The presence of the H-T electrons leads to the significant increase of the REs. This effect has been discussed in several simulations [18,[21][22][23] and experiments [15,24,25].…”
Section: Introductionmentioning
confidence: 89%
“…The presence of the H-T electrons leads to the significant increase of the REs. This effect has been discussed in several simulations [18,[21][22][23] and experiments [15,24,25].…”
Section: Introductionmentioning
confidence: 89%
“…Some qualitative trends in RE seed formation can be inferred from RE plateau current JT-60U, ASDEX-U, and JET have observed data supporting a B ∼ 2 T toroidal field threshold for RE seed formation [206,235,243], leading to speculation that excitation of whistler waves could prevent RE formation below B = 2 T [158]. However, later experiments in JET [244], KSTAR [245], TEXTOR [246], and J-TEXT [247] found that there is no clear toroidal field threshold, so that B = 2 T is not a prerequisite for RE formation. Nevertheless, a robust trend is observed across all machines that higher toroidal magnetic field does elevate the RE plateau levels.…”
Section: E Re Seed Formation During Tqmentioning
confidence: 99%
“…Here, n e is the electron density and lnΛ is the Coulomb logarithm. Several mechanisms can cause electrons to run away, including the Dreicer generation, [9,10] hot tail RE generation, [11][12][13][14] RE avalanching, [15] tritium decay, [16] radio-frequency wave heating [15,17] and Compton scattering of γ-rays from the activated wall. During the flattop, the Dreicer generation is the dominant primary RE mechanism and creates adequate RE seed population which is further amplified by the secondary RE generation named avalanche mechanism.…”
Section: Introductionmentioning
confidence: 99%